1986
DOI: 10.1177/004051758605600807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strain Rate and Gauge Length on the Failure of Ultra-High Strength Polyethylene Fibers

Abstract: Ultra-high strength polyethylene filaments taken from a single spool of yarn were examined for strain rate and gauge length effects. As noted in previous research, high strength polyethylene exhibits pronounced strain rate effects that may be seen in strength changes, stress-strain behavior, and and topography of the fracture zones. Unlike most polymeric fibers, ultra-high strength polyethylene seems to exhibit no gauge length effects over the range from 10 to 200 mm, holding the strain rate constant. This lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 8 publications
5
53
0
3
Order By: Relevance
“…In general, the stress-strain behavior of UHMWPE fiber is increasingly linear with increasing strain rate [3,6,9]. The average behavior of 5 and 10 mm gage length samples is shown in Fig.…”
Section: Shape Of Stress-strain Curves With Respect To Strain Ratementioning
confidence: 91%
See 2 more Smart Citations
“…In general, the stress-strain behavior of UHMWPE fiber is increasingly linear with increasing strain rate [3,6,9]. The average behavior of 5 and 10 mm gage length samples is shown in Fig.…”
Section: Shape Of Stress-strain Curves With Respect To Strain Ratementioning
confidence: 91%
“…For each sample, about 10-20 diameter measurements were taken at different locations along the fiber and were averaged and used as fiber diameter in subsequent stress calculations. While some studies have suggested that UHMWPE fiber lacks roundness and that vibrometry methods are desirable to obtain cross-sectional area measurements [9], Russell et al [3] showed that Dyneema SK76 single fibers were fairly circular in cross-section. Additionally, vibrometry techniques are limited to samples longer than about 50 mm, which becomes problematic when trying to study the gage length dependence on tensile strength and the high-rate properties of fibers which require much shorter gage length samples [5,[9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the stress-strain behavior of UHMWPE fiber is increasingly linear with increasing strain rate (3,6,9). The average behavior of 5-and 10-mm-gage-length samples is shown in figure 8.…”
Section: Shape Of Stress-strain Curves With Respect To Strain Ratementioning
confidence: 96%
“…These self-spun UHMWPE fibers had strengths of 0.4-1.2 GPa, which are considerably weaker than Dyneema and Spectra fibers that fail at stresses of 2.9-4.0 GPa depending on the fiber type (7,8). Capstan-style grips that are typically used in yarn testing have also been used for UHMWPE single fibers (9). However, the exact gage length of specimens in capstan experiments is difficult to determine, which affects ultimate strain and measured modulus values.…”
Section: Introductionmentioning
confidence: 99%